Swami Vivekananda 'S Contribution In Politics (Journal of Namibian Studies : History Politics Culture, 2023)
This research paper delves into the multifaceted contributions of Swami Vivekananda to Indian politics during the late 19th and early 20th centuries. While primarily known as a spiritual leader and philosopher, Vivekananda's ideas and activism had a profound impact on shaping the political landscape of India. The paper examines his influence on political thought, his engagement with prominent political figures of his time, and the enduring legacy of his ideas in contemporary Indian politics.Unveiling the intricate tapestry of his political philosophy, the research elucidates Vivekananda's fusion of spiritual ideals with pragmatic political thought. Investigating his engagements with contemporaneous political leaders and assessing the enduring resonance of his ideas, this abstract sheds light on the singular and often overlooked facets of Vivekananda's contributions to the political discourse of late 19th and early 20th century India.The paper examines his influence on political thought, his engagement with prominent political figures of his time, and the enduring legacy of his ideas in contemporary Indian politics.By shedding light on the nuanced intersections of spirituality and politics in Vivekananda's ideology, this abstract provides a glimpse into the unique facets of his influence on Indian politics.this abstract illuminates the distinctive contours of Vivekananda's contribution to the political landscape. Through this unconventional lens, the research aims to capture the essence of Vivekananda's influence on Indian politics during a transformative period in its history.